Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To simplify the expression [tex]\(\frac{\left(a^8 a^6\right)^{\frac{1}{7}}}{a^2}\)[/tex], follow these steps:
1. Combine the exponents inside the parentheses:
[tex]\[ a^8 \cdot a^6 = a^{8+6} = a^{14} \][/tex]
2. Apply the outer exponent to the result:
[tex]\[ \left(a^{14}\right)^{\frac{1}{7}} = a^{14 \cdot \frac{1}{7}} = a^2 \][/tex]
3. Divide by the denominator exponent:
[tex]\[ \frac{a^2}{a^2} = a^{2-2} = a^0 \][/tex]
4. Simplify the final result:
[tex]\[ a^0 = 1 \][/tex]
Thus, the simplified expression is [tex]\(1\)[/tex].
1. Combine the exponents inside the parentheses:
[tex]\[ a^8 \cdot a^6 = a^{8+6} = a^{14} \][/tex]
2. Apply the outer exponent to the result:
[tex]\[ \left(a^{14}\right)^{\frac{1}{7}} = a^{14 \cdot \frac{1}{7}} = a^2 \][/tex]
3. Divide by the denominator exponent:
[tex]\[ \frac{a^2}{a^2} = a^{2-2} = a^0 \][/tex]
4. Simplify the final result:
[tex]\[ a^0 = 1 \][/tex]
Thus, the simplified expression is [tex]\(1\)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.